OPTICAL PROPERTIES AND TOPOLOGY OF NANOCRYSTALLINE STRUCTURES BASED ON LEAD TELLURIDE: MODEL APPROACHES - Малашкевич, Георгій Юхимович; Фреїк, Дмитро Михайлович; Яворський, Ярослав Святославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Numerical simulation of fields in a limited area of two-dimensional planar and linear aggregates of semiconductor nanoparticles PbTe. The concentration effects of the eclipse and enlightenment in the transmission spectra of monolayers. The dependence of the spectral characteristics of the degree of ordering of the nanostructures.